Cálculo diferencial e integral e geogebra: ferramentas para o ensino da física na educação básica - DIAS, Antonio Alberto de Sousa (2016)
The objective of this paper is to present a proposed approach of Di erential and Integral Calculus in Basic Education to assist in learning of Physics. As a tool we use the software of Dynamic Geometry, The Geogebra, enabling through construction and graphical analysis, working intuitive concepts of speed, average and instantaneous acceleration, to formalize concepts of average rate of change and instanteneous variation of functions, among others. The suggested approach aids in the understanding of physical phenomena, because it is through the Di erential and Integral Calculus that we de ne the quantities involved in the Kinematics.